Dermal Autografts in Plastic Surgery: Advances, Techniques, and Clinical Outcomes - Lisset Guadalupe Hernández Torres; Atziri Verenice Sánchez Contreras; Josue Hernandez Acoltzi; María Guadalupe Cuecuecha Avila (International Journal of Medical Science and Clinical Research Studies, 2024)
The utilization of dermal autografts in plastic surgery has evolved significantly over the past few decades, offering a versatile and reliable method for the reconstruction of various tissue defects. This article reviews the current advancements in dermal autografting, with a focus on the latest surgical techniques, integration with regenerative medicine, and the clinical outcomes observed in diverse patient populations. We discuss the biological basis of autograft survival and integration, highlight innovative approaches to enhance graft viability, and analyze complications associated with these procedures. The article also explores the role of autologous dermal grafts in aesthetic and reconstructive surgery, providing insights into future directions for research and clinical practice.